Anthropometry Between the External Urethral Orifice and the Vaginal Introitus in Vaginism - Carla Maria de Abreu Pereira; Caroline Schmiele Namur; Sônia Maria Rolim Rosa Lima; Vera Lúcia dos Santos Alves (European Medical Journal, 2019)
Introduction: Some of the factors that may be associated with and influence vaginismus and female sexual function have already been studied, such as repressive education, religious teaching, cultural values, and anatomical changes; however, no studies exist that have analysed the measurement between the external urethral orifice and the vaginal introitus in the search for differences between women with and without the diagnosis of vaginismus. Objective: To verify the urethro-vaginal anthropometric relation in women with and without vaginismus. Method: This was a cross-sectional study, approved by the Ethics Committee and registered in clinical trials, conducted from February to August 2017. Sixty women were evaluated, aged 18-40 years old and all of whom were nulliparous, heterosexual, and sexually active. They were divided into two groups: Group I (women with vaginismus, n=30) and Group II (without vaginismus, n=30). Using an inelastic tape measure, the distance between the external urethral orifice and the inferior border of the vaginal introitus was checked in both groups. Results: In Group I, the mean distance between the urethral orifice and the inferior border of the vaginal introitus was 0.69 cm. In Group II, the mean was 1.46 cm, with p<0.001 demonstrated in the comparison for the difference between the groups. Conclusion: A significant difference was observed in the distance between the external urethral orifice and the inferior border of the vaginal introitus in women with and without vaginismus. This anatomical finding may be involved with the evolution of vaginismus.